MPU KUTURAN BERJASA DALAM MENJAGA ADAT BUDAYA DAN AGAMA HINDU - I WAYAN SUARJAYA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The village of Pakraman from the start of its formation has shown its role in society. The village of Pakraman as the backbone remains the establishment of Indigenous, Cultural and Hindu Religion in Bali in particular. Broadly speaking the role of Desa Pakraman can be grouped as the backbone of unity and the unity of the village community, especially in the field;1). The role of Desa Pakraman in the religious social field. As the implementation of Tri Hita Karana in the field of Parhyangan, namely maintaining good relationship between kerama with God through in the field of upakara and religious ceremony always be borne together. Like the implementation of Piodalan day at Pura, the implementation of religious festivals is always shared by Pakraman village. The role of the village of Pakraman in the religious social field, as a public servant in the implementation of Panca Yadnya done by the community, always supported by the Village Pakraman, especially Marriage Ceremony, Pengabenan, Ceremony mettah and so forth 2. The role of Desa Pakraman in the social field. As the implementation of Tri Hita Karana in the field of socio-culture, more about society and environment. The role of community is to organize a harmonious relationship between villagers. The role of Desa Pakraman seen from the social community is very visible from the philosophy of life as stipulated in the collective agreement as well as daily rules such as